Climate and development modulate the metabolome and antioxidative system of date palm leaves. (3rd August 2019) - Du, Baoguo; Kruse, Joerg; Winkler, Jana Barbro; Alfarray, Saleh; Schnitzler, Joerg-Peter; Ache, Peter; Hedrich, Rainer; Rennenberg, Heinz
Abstract : High temperatures of summer climate markedly impact the foliar metabolome and the antioxidative system of date palms, with young leaves being more responsive than mature leaves. Abstract: Date palms are remarkably tolerant to environmental stresses, but the mechanisms involved remain poorly characterized. Leaf metabolome profiling was therefore performed on mature (ML) and young (YL) leaves of 2-year-old date palm seedlings that had been grown in climate chambers that simulate summer and winter conditions in eastern Saudi Arabia. Cultivation under high temperature (summer climate) resulted in higher YL H2 O2 leaf levels despite increases in dehydroascorbate reductase (DHAR) activities. The levels of raffinose and galactinol, tricarboxylic acid cycle intermediates, and total amino acids were higher under these conditions, particularly in YL. The accumulation of unsaturated fatty acids, 9, 12-octadecadienoic acid and 9, 12, 15-octadecatrienoic acid, was lower in ML. In contrast, the amounts of saturated tetradecanoic acid and heptadecanoic acid were increased in YL under summer climate conditions. The accumulation of phenolic compounds was favored under summer conditions, while flavonoids accumulated under lower temperature (winter climate) conditions. YL displayed stronger hydration, lower H2 O2 levels, and more negative δ 13 C values, indicating effective reactive oxygen species scavenging. These findings, which demonstrate the substantial metabolic adjustments that facilitate tolerance to the high temperatures in YL and ML, suggest that YL may be more responsive to climate change.